Ustekinumab - Murat Borlu (Galenos Publishing House, 2022)
Ustekinumab is an antagonistic human monoclonal immunoglobulin G1 antibody that targets p40, a common subunit of interleukin-12 (IL-12) and IL-23. In clinical trials, 66-81% of the patients using ustekinumab achieved a PASI75 response. Its long drug survival time has been found remarkable in real-world experiences. Other advantages of ustekinumab include ease of use in obese patients as its dose can be adjusted according to body weight and its administration every 12 weeks in the maintenance period.